Manajemen Pendidik dan Tenaga Kependidikan di TK Negeri 3 Taliwang - Elya Siska Anggraini; Wilde Dosta Cristina Silalahi; Tsalitsa Gunawan Silalahi; Indah Pefrianti Dalimunthe; Erika Sihite (CV. ITTC INDONESIA, 2026)
Educators and educational staff are important components in the implementation of early childhood education. The quality of educator management greatly influences the success of the learning process and children's optimal development. This study aims to analyze the implementation of educator and educational staff management at TK Negeri 3 Taliwang and to identify its implications, supporting factors, and inhibiting factors. The research method used is a literature study by reviewing various scientific sources such as journals, books, and documents related to the research topic. The results show that the management of educators and educational staff includes planning, recruitment, placement, competency development, and performance evaluation. Good management implementation can improve the quality of educational institutions, enhance teacher professionalism, and support more effective learning processes. However, several challenges still exist, such as the limited number of professionally qualified teachers and the lack of continuous training for educators. Therefore, support from various parties is needed to improve the quality of educator and educational staff management in early childhood education institutions.